2018
DOI: 10.1530/ec-17-0349
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-permeable microwell device maintains islet mass and integrity during shipping

Abstract: Islet transplantation is currently the only minimally invasive therapy available for patients with type 1 diabetes that can lead to insulin independence; however, it is limited to only a small number of patients. Although clinical procedures have improved in the isolation and culture of islets, a large number of islets are still lost in the pre-transplant period, limiting the success of this treatment. Moreover, current practice includes islets being prepared at specialized centers, which are sometimes remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…41,42 The porous structure of a microwell scaffold could allow free permeation of oxygen and nutrients that are important for maintaining cell viability by alleviating hypoxia stress, importing glucose and secreting insulin. 43,44…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The porous structure of a microwell scaffold could allow free permeation of oxygen and nutrients that are important for maintaining cell viability by alleviating hypoxia stress, importing glucose and secreting insulin. 43,44…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature demonstrated that microwells ~400 µm in diameter maintained functional human islets for 7 days ( 46 ). Another study showed that 500 µm-microwells effectively segregated islets for the short-term, with a shaking culture condition mimicking islet shipping ( 47 ); however, multiple islets in a well were observed, which indicates the importance of islet-size-specific microwells. We addressed the issue by preparing different-sized microwells, minimizing the fusion of large islets with a simple and practical approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jiang et al [330] incorporated 0.1 %–0.25 % dexamethasone into a PDMS-based 3D scaffold to suppress the immune response, ultimately enhancing blood glucose levels and suppressing inflammatory pathways on M2 macrophages. Several recent studies utilized PDMS scaffolds as an oxygen vehicle for transplanted islets [331] , [332] . To mitigate the negative effects induced by hypoxic conditions post-transplantation at the extra-hepatic site, Liang et al [333] incorporated calcium peroxide in the PDMS scaffold.…”
Section: Biomaterialsmentioning
confidence: 99%